Padronização de modelo de ligadura da artéria uterina em ratas não-grávidas, seus efeitos sobre a isquemia uterina direta e suas repercussões reprodutivas - Vasconcelos Neto, José Ananias (2009)
The obstruction of the uterine arteries promotes ischemia or necrosis in the uterus. However it is not known how strongly these injuries occur. The objectives of this study are to describe and standardize a technique of right uterine artery ligation (UAL) in non-pregnant rats and to evaluate the effects of this model in the uteri and ovaries of female rats. An experimental study using 64 rats, 48 females and 16 males (Rattus norvegicus, albino variety) mature, with proven fertility. The rats were randomly allocated into 8 groups of six individuals. Four groups were subjected to the technique of right UAL and sacrificed on days 1, 7, 14 and 21 after the procedure. Other 3 groups were mated on days 1, 7 and 14 after the UAL, and compared with the control group regarding fertility. After sacrifice, ovaries and the hemi-uteri, were removed for histological analysis wich was carried out histological analysis, which evaluated the uteri and the congestion, hemorrhage, interstitial edema and loss of cell cohesion through a score ranging from 0 to 3. Ovaries were evaluated according to the number of follicles and corpora lutea. For statistical analysis we used SPSS software (Statistical Package for Social Sciences) version 13.0, p <0.05 was considered statistically significant. The research project was submitted to the Ethics Committee on Animal Research (ECAR) Federal University of Ceará, under the number 90/08. The model of the technique was performed in non-pregnant rats using ligation in the lower portion of the right uterine artery, keeping the left hemi-uteri (LHU) as control. At no time during periods of ischemia established (1, 7, 14 and 21 days) there was any difference between the histological scores of ischemia of the right hemi-uteri (RHU) distal and proximal (p> 0.05). The histological scores of ischemia of the right hemi-uteri over time increased significantly from day 7 (p = 0.003), just as occurred with the left hemi-uteri (p = 0.001). The only significant difference observed when comparing the scores of the right hemi-uteri and left occurred on day 1 after UAL (p = 0.026), due to congestion. The left ovary showed no changes in the number of follicles and corpora lutea after UAL, and the right ovary showed a number of follicles and corpora lutea similar to control from the 21th day of UAL. The percentage of pregnant rats that were subjected to ischemia was 44.4%, compared with 100% of control rats that became pregnant (p = 0.024). There was also a reduction in the average number of fetuses per mother (p = 0.029). It can be concluded that the model established was effective and highly reproducible, and histological changes found in the uteri are mild. As to ovulatory function, one can say that the number of follicles and corpora lutea of the right ovaries, after 21 days, remained similar to the left (control). Fertility, however, was reduced after the establishment of this technique.